Comparison of heavy ion and pulsed laser single-event effect test data for analogue and digital devices - Häkkinen, Annika (2024)
This thesis examines the comparison of heavy ion and pulse laser SEE testing in analogue (LM124 operational amplifier) and digital parts (23LCV512 SRAM). The testing was conducted for Radtest Ltd and the goal was to collect data for their pulsed laser testing system, SEREEL2. The heavy ion testing was done in Heavy Ion Facility at UCLouvain, Belgium. For the LM124, SET cross sections were calculated and presented as a function of LET. These results showed that the saturation started from around the LET of 30 MeV/(mg/cm ) which was similar result to the literature. The pulse shapes from the laser testing were connected to specific transistors with the layout of the device and could be compared between heavy ion data. This comparison showed that the pulse shapes from the heavy ions were possible to be connected to specific transistors. The SET cross sections were calculated also for the most common pulse shape groups and they were presented with the different values of LET. For the 23LCV512, SEU cross sections – for both heavy ion and laser testing – were calculated and presented as a function of LET and laser pulse energy. Unlike with LM124, for the 23LCV512 the same test method did not transfer as well between heavy ion and laser testing. Thus the resulting SEUs were not triggered from the same area resulting in different formats of SEUs. As a solution for this, options like backside testing were discussed.